2020
DOI: 10.1155/2020/5316364
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Sleep Health among Adolescents: The Role of Sex, Age, and Migration

Abstract: Background. Disparities in sleep disturbances have been described in adults; nevertheless, among adolescents, data have yielded conflicting results. Therefore, analyses of our cohort study of 500 urban, normally developed Hispanic adolescents (10–18 years), aim to determine if rates of sleep debt differ between: (a) male and female adolescents, (b) US-born Hispanics and first-generation immigrant ethnic counterparts, and (c) specific activities that these teens trade for sleep. Participants’ weekday and weeken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
5
8
0
Order By: Relevance
“…Survey results also indicated that more than half of the participants (57.15%) do not reach the sleep duration recommendation by NSF [ 35 ] in the current study. The result is consistent with previous Chinese studies, in which insufficient sleep prevalence ranges from 31.3% to 66.0% [ 15 , 19 , 49 ], and higher than those studies from Western countries with 14.2% to 50.0% prevalence [ 16 , 50 , 51 ]. The differences in the prevalence of insufficient sleep may be related to the unique culture and educational system in China, where education is based on Confucian principles addressing the successful scholarship of children and adolescents [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Survey results also indicated that more than half of the participants (57.15%) do not reach the sleep duration recommendation by NSF [ 35 ] in the current study. The result is consistent with previous Chinese studies, in which insufficient sleep prevalence ranges from 31.3% to 66.0% [ 15 , 19 , 49 ], and higher than those studies from Western countries with 14.2% to 50.0% prevalence [ 16 , 50 , 51 ]. The differences in the prevalence of insufficient sleep may be related to the unique culture and educational system in China, where education is based on Confucian principles addressing the successful scholarship of children and adolescents [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, it must be considered that most of the participants in that study were older than the participants included in our study. Alternatively, the study of Miguez, et al [39] showed no differences in hours of sleep between men and women with similar ages to those reported herein. These discrepancies in the hours of sleep may be explained by the characteristics of the population, as well as the increased access to video games for men compared to women [40,41].…”
Section: Discussionsupporting
confidence: 65%
“…Other variables should be considered while investigating sleep. Sex has been found to play an important role in the context of sleep among adolescents [ 6 , 7 , 12 , 15 , 32 , 33 , 34 ]. Studies have reported mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported mixed results. However, in girls and boys, different sleep habits, sleep durations, as well as sleep needs were observed [ 32 , 33 , 34 ]. Adolescents’ age is also a relevant factor in sleep problems [ 16 ] and sleep-onset difficulties [ 15 ], which increase with age.…”
Section: Introductionmentioning
confidence: 99%